2016
DOI: 10.1182/blood-2016-02-696310
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous calreticulin mutations in patients with myelofibrosis lead to acquired myeloperoxidase deficiency

Abstract: Key Points• Acquired MPO deficiency in patients with MPN is uniquely associated with homozygous CALR mutations.• In line with a posttranscriptional defect, MPO deficiency results from reduced MPO protein levels, but not from decreased MPO mRNA.The pathogenesis of acquired myeloperoxidase (MPO) deficiency, a rare phenomenon observed in patients with Philadelphia chromosome-negative myeloproliferative neoplasms (MPNs), is unknown. MPO is a glycoprotein (GP) chaperoned by calreticulin (CALR) in the endoplasmic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 26 publications
5
38
0
Order By: Relevance
“…33 In contrast to JAK2V617F, the VAF for mutant CALR in ET is high, on average around 40%. 10 In rare cases of ET, the VAF can be lower, but almost never below 15%.…”
Section: Mutations In the Calreticulin Gene: Calrmentioning
confidence: 96%
“…33 In contrast to JAK2V617F, the VAF for mutant CALR in ET is high, on average around 40%. 10 In rare cases of ET, the VAF can be lower, but almost never below 15%.…”
Section: Mutations In the Calreticulin Gene: Calrmentioning
confidence: 96%
“…Mutant CALR allele frequencies that are suggestive of homozygosity are rare in MPN patients; only three examples of apparent homozygosity were detected in 286 CALR ‐mutated cases (from a cohort of 1215 patients with ET or MF) (Klampfl et al , ). Most mutation‐homozygous individuals have primary or post‐thrombocythaemic MF (Rumi et al , ; Theocharides et al , ); the case reported here (Patient B), and one other (Klampfl et al , ), were diagnosed with ET. Mutation homozygosity in Patient B was not the result of an independent mutation event within her remaining wildtype CALR allele, but rather by mitotic recombination that produced a region of uniparental disomy (UPD) within chromosome 19 that included the CALR locus (Fig B).…”
Section: Discussionmentioning
confidence: 63%
“…This event would have preceded diagnosis, as most of the clonogenic progenitors assessed at that time were already mutation‐homozygous (Fig A). The clinical consequences of CALR mutation homozygosity remain unclear, although a subgroup of MF patients (6 of 81), most of whom were CALR mutation‐homozygous, were shown to have acquired myeloperoxidase (MPO) deficiency (Theocharides et al , ). However, this disorder was absent in 94 patients with ET, so it is unlikely to be caused by CALR mutation‐homozygous alone.…”
Section: Discussionmentioning
confidence: 99%
“…The proMPO protein is then exported to the Golgi whereupon further processing takes place prior to the storage of MPO in azurophilic granules . Recent studies have revealed that homozygous mutations in the calreticulin gene ( CALR ) lead to acquired MPO deficiency; these individuals have reduced MPO protein, but normal MPO mRNA levels, supporting a posttranscriptional defect in MPO production . Further studies are required to understand how JAGN1 regulates MPO expression in neutrophils, but our findings do not support a role of JAGN1 in modulating N ‐glycosylation of MPO.…”
Section: Discussionmentioning
confidence: 99%